Kualitas hidup pasien Gagal Jantung Kongestif (GJK) Berdasarkan karakteristik Demografi - Akhmad, Arif Nur (Jurnal Keperawatan Soedirman, 2016)
Patients of Congestive Heart Failure (CHF) basically have some symptoms, such as fatigue, dyspnea, and high mortality contributing to affects on their quality of life. Various factors may be related to quality of life, such as age, gender, education, occupation, and NYHA (New York Heart Association) level. This research aims at identifying and explaining demography factors related to quality of life on Congestive Heart Failure (CHF) patients. This research uses descriptive correlation and cross sectional design with 62 patients of Dr. Sardjito Hospital Yogyakarta as the sample. Data obtained by using demographic data questionnaire and the SF-36 version of Indonesian. Data were analyzed with Spearman's test. The results showed respondents with a median age 51.14 years (SD = 12.40). Most patients are male (71%), unemployed (69%). and less educated (53%). Quality of life has correlation with NYHA class (p value= 0,001), educational (p value= 0,001), and age (p value= 0,014). There is no correlation between quality of life and gender and occupation. It can be concluded that NYHA class, educational, and age are independent factors related to quality of life